Effect of twin boundary spacing on mechanical and structural properties of nano polycrystalline bulk Au element - Kazanc, Sefa; Baykara, Oktay (Springer Heidelberg, 2025)
This study investigates the mechanical and structural properties of nano-polycrystalline bulk Au under uniaxial compression and tension with varying twin boundary spacing (TBS) using molecular dynamics (MD) simulations and the Embedded Atom Method (EAM). Results reveal a Hall-Petch (HP) effect during compression, transitioning to a reverse HP effect beyond a critical TBS, while only the HP effect is observed during tension. Dislocation mechanisms are significantly influenced by TBS: at small TBS values, dislocations slide along twin boundaries (TB), whereas at larger TBS, they intersect TB. These behaviors explain the transition from hardening to softening in yield strength. Additionally, the study highlights the formation and evolution of partial dislocations at grain boundaries (GB) and TB during both deformation modes. The findings enhance the understanding of deformation mechanisms in nanostructured materials, providing insights into optimizing mechanical properties through twin boundary engineering.
Keywords: Nano-polycrystalline; Twin boundary spacing; Hall-Petch effect; Molecular Dynamics